Pengaruh Budaya Organisasi, Komitmen Organisasi Dan Penilaian Kinerja Terhadap Turnover Intention Pada Zam Zam Hotel & Convention Kota Batu - Tri Wijayanti; Muhammad Mansur; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This research was conducted at Zam Zam Hotel & Convention Kota Batu. In this research, the type of research used is quantitative research where the data is expressed in numbers and analyzed by statistical techniques. The purpose of this study was to determine the effect of organizational culture, organizational commitment, and performance appraisals on turnover intention. The independent variables used are organizational culture, organizational commitment, and performance appraisal, while the dependent variable is turnover intention. The sample used in this study were 44 respondents who were employees at Zam Zam Hotel & Convention Kota Batu. The data collection technique used a questionnaire. The analytical method used is the instrument test, morality test, multiple linear regression analysis, classical assumption test, test of determination, test f and t test using the help of computer software SPSS 25 data processing. The results of this study indicate that organizational culture, organizational commitment, and performance appraisals simultaneously affect turnover intention. In addition, each independent variable, organizational culture, organizational commitment, and performance appraisal partially also has a positive and significant effect on turnover intention. Keywords: Organizational Culture, Organizational Commitment, Performance Appraisal, Turnover Intention.